Informação Bibliográfica - Isabel Leonor Teles (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2008)
LAVERACK, Glenn - Promoção de Saúde: Poder e Empoderamento. Loures: Lusodidacta, 2008. ISBN 978-989-8075-09-3